High-adhesion epoxy anticorrosive paint and preparation method thereof
By organically modifying carboxylate graphene, its dispersion performance and capacity-enhancing effect in the epoxy resin system are improved, and the problem of high zinc powder consumption in existing zinc-containing coatings is solved, and epoxy anticorrosion coatings with high adhesion, excellent mechanical properties and good corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411351086.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The high amount of zinc powder used in existing zinc-containing coatings leads to high consumption of metal zinc resources, serious environmental pollution and a threat to human health. Graphene is difficult to disperse well in the coatings, resulting in limited anticorrosion performance.
By organically modifying carboxy graphene, the dispersion performance of graphene in the epoxy resin system is significantly improved, and the capacity-enhancing effect between graphene and the epoxy resin system is exerted, thereby preparing high adhesion epoxy anticorrosion coatings.
It significantly increases the adhesion, mechanical properties and corrosion resistance of composite coatings, reduces the amount of zinc powder, and reduces environmental pollution and resource consumption.
Smart Images

Figure BDA0005062381030000091 
Figure BDA0005062381030000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings and relates to a high-adhesion epoxy anticorrosive coating and a preparation method thereof. Background Art
[0002] At present, zinc-containing coatings have become one of the most critical and widely used primers in steel protection; their anti-corrosion properties are mainly reflected in electrochemical protection, shielding effect and the self-healing ability of the coating. However, the amount of zinc powder used in these coatings is extremely high (can exceed 80%). This high zinc content coating not only consumes a large amount of metallic zinc resources, but also easily causes environmental pollution and threatens human health. Therefore, the development direction of epoxy zinc-containing primers is to improve the use efficiency of zinc powder in the paint film, while maintaining or enhancing its original protective effectiveness and reducing the amount of zinc powder. To achieve this goal, carbon-based nanofillers can be added to zinc-containing coatings.
[0003] Graphene is a material with a unique two-dimensional structure, consisting of a single layer of carbon atoms arranged in a hexagonal pattern. Due to its excellent physical and chemical properties, graphene has a wide range of applications in many fields, especially in anti-corrosion fillers. Graphene's high conductivity and excellent mechanical properties make it an ideal anti-corrosion material. It can effectively block the penetration of corrosive media, thereby protecting the substrate from corrosion. In addition, graphene also has extremely high thermal and chemical stability, and can maintain its performance in harsh environments. Therefore, as an anti-corrosion filler, graphene can not only extend the service life of the coating, but also reduce maintenance costs, with significant economic benefits and environmental value. It is a chemically inert two-dimensional sheet structure material. However, graphene has an extremely high diameter-to-thickness ratio and specific surface area, which also makes it easy to agglomerate, and it is difficult to be well dispersed in the coating to fully play its role, resulting in limited anti-corrosion performance of the coating. Summary of the invention
[0004] The purpose of the present invention is to provide a high-adhesion epoxy anti-corrosion coating and a preparation method thereof. The present invention significantly improves the dispersion performance of graphene in an epoxy resin system by organically modifying carboxyl graphene, and exerts a volume expansion effect between graphene and the epoxy resin system, thereby significantly increasing the adhesion, mechanical properties and corrosion resistance of the composite coating.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A high-adhesion epoxy anticorrosive coating comprises the following components by weight: 62-70 parts of epoxy resin, 5-8 parts of liquid petroleum resin, 7-12 parts of fumed silica, 6-8 parts of nano-montmorillonite, 5-8 parts of silane coupling agent, 0.1-0.3 parts of defoaming agent, 0.2-0.3 parts of epoxy curing agent, 7-10 parts of wetting agent, 0.5-1 parts of leveling agent, 7-10 parts of rutile titanium dioxide, 2-6 parts of aluminum silver paste, 6-9 parts of modified graphene and 70-80 parts of deionized water.
[0007] As a preferred technical solution of the present invention, the epoxy resin is bisphenol A epoxy resin; and the silane coupling agent is silane coupling agent KH550.
[0008] As a preferred technical solution of the present invention, the wetting agent is polydimethylsiloxane; the defoaming agent is one or more of aliphatic polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ether, castor oil polyoxyethylene ether and fatty amine polyoxyethylene ether.
[0009] As a preferred technical solution of the present invention, the epoxy curing agent is methyl hexahydrophthalic anhydride; and the leveling agent is BYK-111.
[0010] The present invention discloses a method for preparing the modified graphene, comprising the following steps:
[0011] 1) In an inert atmosphere, carboxylated graphene, anhydrous ethanol and eugenol are stirred and dispersed, a catalyst is added, heated and stirred, filtered, a solid is taken out for washing, and placed in an oven for vacuum drying to obtain prefabricated particles;
[0012] 2) The prefabricated particles and anhydrous ethanol are mixed and then subjected to ultrasonic treatment, and a reaction monomer and a photoinitiator are added, stirred and mixed, filtered, and a solid is taken for washing, and placed in an oven for vacuum drying to obtain modified graphene.
[0013] As a preferred technical solution of the present invention, in step 1), the inert atmosphere is a nitrogen atmosphere; the stirring and dispersing is stirring at a speed of 700-800 r / min for 30-40 min; the heating and stirring is stirring at a temperature of 100-110°C and a speed of 400-500 r / min for 2-3 h; the washing is washing three times with ethanol; and the vacuum drying is drying at a temperature of 80-90°C to constant weight.
[0014] As a preferred technical solution of the present invention, in step 1), the mass ratio of the carboxylated graphene, anhydrous ethanol, eugenol and catalyst is 30-33:90-100:10-13:0.44-0.50; the catalyst is p-toluenesulfonic acid;
[0015] As a preferred technical solution of the present invention, in step 2), the ultrasonic treatment is ultrasonic treatment at a frequency of 200-300W for 12-20min; the stirring and mixing is reaction at a temperature of 32-38°C under 365nm ultraviolet irradiation for 5-7h; the washing is washing three times with ethanol; and the vacuum drying is drying at a temperature of 80-90°C to constant weight.
[0016] As a preferred technical solution of the present invention, in step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, reaction monomer and photoinitiator is 40-50:140-160:4.2-6.0:0.22-0.30; the reaction monomer is prepared by mixing thioglycerol and p-fluorobenzenethiophenol in a mass ratio of 3:1; and the photoinitiator is photoinitiator 1173.
[0017] The invention discloses a method for preparing a high-adhesion epoxy anticorrosion coating. The method comprises the following steps: adding epoxy resin, fumed silica, nano-montmorillonite, rutile titanium dioxide, silane coupling agent, liquid petroleum resin, wetting agent, aluminum silver paste and modified graphene into deionized water, stirring evenly at a high speed of 900-1100 r / min, then adding a leveling agent, an epoxy curing agent and a defoaming agent, stirring evenly, and obtaining the high-adhesion epoxy anticorrosion coating.
[0018] Beneficial effects of the present invention:
[0019] The present invention significantly improves the dispersion performance of graphene in the epoxy resin system by organically modifying the carboxyl graphene, and exerts the volume expansion effect between the graphene and the epoxy resin system, thereby significantly increasing the adhesion, mechanical properties and corrosion resistance of the composite coating. DETAILED DESCRIPTION
[0020] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0021] Example 1
[0022] A high-adhesion epoxy anticorrosive coating comprises the following components by weight: 62 parts of epoxy resin, 5 parts of liquid petroleum resin, 7 parts of fumed silica, 6 parts of nano-montmorillonite, 5 parts of silane coupling agent, 0.1 parts of defoaming agent, 0.2 parts of epoxy curing agent, 7 parts of wetting agent, 0.5 parts of leveling agent, 7 parts of rutile titanium dioxide, 2 parts of aluminum silver paste, 6 parts of modified graphene and 70 parts of deionized water;
[0023] Among them, the epoxy resin is bisphenol A epoxy resin; the silane coupling agent is silane coupling agent KH550; the wetting agent is polydimethylsiloxane; the defoaming agent is alkylphenol polyoxyethylene ether; the epoxy curing agent is methyl hexahydrophthalic anhydride; and the leveling agent is BYK-111.
[0024] The preparation method of the modified graphene comprises the following steps:
[0025] 1) In an inert atmosphere, carboxylated graphene, anhydrous ethanol and eugenol are stirred and dispersed, a catalyst is added, heated and stirred, filtered, a solid is taken out for washing, and placed in an oven for vacuum drying to obtain prefabricated particles;
[0026] 2) The prefabricated particles and anhydrous ethanol are mixed and then subjected to ultrasonic treatment, and a reaction monomer and a photoinitiator are added, stirred and mixed, filtered, and a solid is taken for washing, and placed in an oven for vacuum drying to obtain modified graphene.
[0027] In step 1), the inert atmosphere is a nitrogen atmosphere; the stirring and dispersing is stirring at a speed of 700 r / min for 30 minutes; the heating and stirring is stirring at a temperature of 100° C. and a speed of 400 r / min for 2 hours; the washing is washing three times with ethanol; the vacuum drying is dried to constant weight at a temperature of 80° C.; the mass ratio of the carboxylated graphene, anhydrous ethanol, eugenol and catalyst is 30:90:10:0.44; the catalyst is p-toluenesulfonic acid;
[0028] In step 2), the ultrasonic treatment is performed at a frequency of 200 W for 12 minutes; the stirring and mixing is performed under 365 nm ultraviolet irradiation and a temperature of 32° C. for 5 hours; the washing is performed three times with ethanol; the vacuum drying is performed at a temperature of 80° C. to constant weight; the mass ratio of the prefabricated particles, anhydrous ethanol, reaction monomer and photoinitiator is 40:140:4.2:0.22; the reaction monomer is prepared by mixing thioglycerol and p-fluorothiophenol in a mass ratio of 3:1; and the photoinitiator is photoinitiator 1173.
[0029] A method for preparing a high-adhesion epoxy anti-corrosion coating comprises the following steps: adding epoxy resin, fumed silica, nano-montmorillonite, rutile titanium dioxide, silane coupling agent, liquid petroleum resin, wetting agent, aluminum silver paste and modified graphene into deionized water, stirring evenly at a high speed of 900 r / min, then adding a leveling agent, an epoxy curing agent and a defoaming agent, stirring evenly, and obtaining a high-adhesion epoxy anti-corrosion coating.
[0030] Example 2
[0031] A high-adhesion epoxy anticorrosive coating comprises the following components by weight: 65 parts of epoxy resin, 6 parts of liquid petroleum resin, 9 parts of fumed silica, 6.7 parts of nano-montmorillonite, 6 parts of silane coupling agent, 0.17 parts of defoaming agent, 0.23 parts of epoxy curing agent, 8 parts of wetting agent, 0.7 parts of leveling agent, 8 parts of rutile titanium dioxide, 3 parts of aluminum silver paste, 7 parts of modified graphene and 73 parts of deionized water;
[0032] Among them, the epoxy resin is bisphenol A epoxy resin; the silane coupling agent is silane coupling agent KH550; the wetting agent is polydimethylsiloxane; the defoaming agent is alkylphenol polyoxyethylene ether; the epoxy curing agent is methyl hexahydrophthalic anhydride; and the leveling agent is BYK-111.
[0033] The preparation method of the modified graphene comprises the following steps:
[0034] 1) In an inert atmosphere, carboxylated graphene, anhydrous ethanol and eugenol are stirred and dispersed, a catalyst is added, heated and stirred, filtered, a solid is taken out for washing, and placed in an oven for vacuum drying to obtain prefabricated particles;
[0035] 2) The prefabricated particles and anhydrous ethanol are mixed and then subjected to ultrasonic treatment, and a reaction monomer and a photoinitiator are added, stirred and mixed, filtered, and a solid is taken for washing, and placed in an oven for vacuum drying to obtain modified graphene.
[0036] In step 1), the inert atmosphere is a nitrogen atmosphere; the stirring and dispersing is stirring at a speed of 730 r / min for 35 minutes; the heating and stirring is stirring at a temperature of 103° C. and a speed of 430 r / min for 2.5 hours; the washing is washing three times with ethanol; the vacuum drying is dried to constant weight at a temperature of 83° C.; the mass ratio of the carboxylated graphene, anhydrous ethanol, eugenol and catalyst is 31:93:11:0.46; the catalyst is p-toluenesulfonic acid;
[0037] In step 2), the ultrasonic treatment is performed at a frequency of 230 W for 15 minutes; the stirring and mixing is performed under 365 nm ultraviolet irradiation and a temperature of 34° C. for 5.5 hours; the washing is performed three times with ethanol; the vacuum drying is performed at a temperature of 83° C. to constant weight; the mass ratio of the prefabricated particles, anhydrous ethanol, reaction monomer and photoinitiator is 43:147:4.8:0.25; the reaction monomer is prepared by mixing thioglycerol and p-fluorobenzenethiophenol in a mass ratio of 3:1; and the photoinitiator is photoinitiator 1173.
[0038] A preparation method of a high-adhesion epoxy anti-corrosion coating comprises the following steps: adding epoxy resin, fumed silica, nano-montmorillonite, rutile titanium dioxide, silane coupling agent, liquid petroleum resin, wetting agent, aluminum silver paste and modified graphene into deionized water, stirring evenly at a high speed of 967 r / min, then adding a leveling agent, an epoxy curing agent and a defoaming agent, stirring evenly, and obtaining a high-adhesion epoxy anti-corrosion coating.
[0039] Example 3
[0040] A high-adhesion epoxy anticorrosive coating comprises the following components by weight: 67 parts of epoxy resin, 7 parts of liquid petroleum resin, 10 parts of fumed silica, 7.3 parts of nano-montmorillonite, 7 parts of silane coupling agent, 0.23 parts of defoaming agent, 0.27 parts of epoxy curing agent, 9 parts of wetting agent, 0.8 parts of leveling agent, 9 parts of rutile titanium dioxide, 5 parts of aluminum silver paste, 8 parts of modified graphene and 77 parts of deionized water;
[0041] Among them, the epoxy resin is bisphenol A epoxy resin; the silane coupling agent is silane coupling agent KH550; the wetting agent is polydimethylsiloxane; the defoaming agent is alkylphenol polyoxyethylene ether; the epoxy curing agent is methyl hexahydrophthalic anhydride; and the leveling agent is BYK-111.
[0042] The preparation method of the modified graphene comprises the following steps:
[0043] 1) In an inert atmosphere, carboxylated graphene, anhydrous ethanol and eugenol are stirred and dispersed, a catalyst is added, heated and stirred, filtered, a solid is taken out for washing, and placed in an oven for vacuum drying to obtain prefabricated particles;
[0044] 2) The prefabricated particles and anhydrous ethanol are mixed and then subjected to ultrasonic treatment, and a reaction monomer and a photoinitiator are added, stirred and mixed, filtered, and a solid is taken for washing, and placed in an oven for vacuum drying to obtain modified graphene.
[0045] In step 1), the inert atmosphere is a nitrogen atmosphere; the stirring and dispersing is stirring at a speed of 760 r / min for 37 minutes; the heating and stirring is stirring at a temperature of 107° C. and a speed of 460 r / min for 2.5 hours; the washing is washing three times with ethanol; the vacuum drying is dried to constant weight at a temperature of 87° C.; the mass ratio of the carboxylated graphene, anhydrous ethanol, eugenol and catalyst is 32:97:12:0.48; the catalyst is p-toluenesulfonic acid;
[0046] In step 2), the ultrasonic treatment is performed at a frequency of 265 W for 15 minutes; the stirring and mixing is performed under 365 nm ultraviolet irradiation and a temperature of 36° C. for 6.5 hours; the washing is performed three times with ethanol; the vacuum drying is performed at a temperature of 87° C. to constant weight; the mass ratio of the prefabricated particles, anhydrous ethanol, reaction monomer and photoinitiator is 47:153:5.4:0.27; the reaction monomer is prepared by mixing thioglycerol and p-fluorothiophenol in a mass ratio of 3:1; and the photoinitiator is photoinitiator 1173.
[0047] A preparation method of a high-adhesion epoxy anti-corrosion coating comprises the following steps: adding epoxy resin, fumed silica, nano-montmorillonite, rutile titanium dioxide, silane coupling agent, liquid petroleum resin, wetting agent, aluminum silver paste and modified graphene into deionized water, stirring evenly at a high speed of 1030 r / min, then adding a leveling agent, an epoxy curing agent and a defoaming agent, stirring evenly, and obtaining a high-adhesion epoxy anti-corrosion coating.
[0048] Example 4
[0049] A high-adhesion epoxy anticorrosive coating comprises the following components by weight: 70 parts of epoxy resin, 8 parts of liquid petroleum resin, 12 parts of fumed silica, 8 parts of nano-montmorillonite, 8 parts of silane coupling agent, 0.3 parts of defoaming agent, 0.3 parts of epoxy curing agent, 10 parts of wetting agent, 1 part of leveling agent, 10 parts of rutile titanium dioxide, 6 parts of aluminum silver paste, 9 parts of modified graphene and 80 parts of deionized water;
[0050] Among them, the epoxy resin is bisphenol A epoxy resin; the silane coupling agent is silane coupling agent KH550; the wetting agent is polydimethylsiloxane; the defoaming agent is alkylphenol polyoxyethylene ether; the epoxy curing agent is methyl hexahydrophthalic anhydride; and the leveling agent is BYK-111.
[0051] The preparation method of the modified graphene comprises the following steps:
[0052] 1) In an inert atmosphere, carboxylated graphene, anhydrous ethanol and eugenol are stirred and dispersed, a catalyst is added, heated and stirred, filtered, a solid is taken out for washing, and placed in an oven for vacuum drying to obtain prefabricated particles;
[0053] 2) The prefabricated particles and anhydrous ethanol are mixed and then subjected to ultrasonic treatment, and a reaction monomer and a photoinitiator are added, stirred and mixed, filtered, and a solid is taken for washing, and placed in an oven for vacuum drying to obtain modified graphene.
[0054] In step 1), the inert atmosphere is a nitrogen atmosphere; the stirring and dispersing is stirring at a speed of 800 r / min for 40 minutes; the heating and stirring is stirring at a temperature of 110° C. and a speed of 500 r / min for 3 hours; the washing is washing three times with ethanol; the vacuum drying is dried to constant weight at a temperature of 90° C.; the mass ratio of the carboxylated graphene, anhydrous ethanol, eugenol and catalyst is 33:100:13:0.50; the catalyst is p-toluenesulfonic acid;
[0055] In step 2), the ultrasonic treatment is performed at a frequency of 300 W for 20 minutes; the stirring and mixing is performed under 365 nm ultraviolet irradiation and a temperature of 38° C. for 7 hours; the washing is performed three times with ethanol; the vacuum drying is performed at a temperature of 90° C. to constant weight; the mass ratio of the prefabricated particles, anhydrous ethanol, reaction monomer and photoinitiator is 50:160:6.0:0.30; the reaction monomer is prepared by mixing thioglycerol and p-fluorothiophenol in a mass ratio of 3:1; and the photoinitiator is photoinitiator 1173.
[0056] A preparation method of a high-adhesion epoxy anti-corrosion coating comprises the following steps: adding epoxy resin, fumed silica, nano-montmorillonite, rutile titanium dioxide, silane coupling agent, liquid petroleum resin, wetting agent, aluminum silver paste and modified graphene into deionized water, stirring evenly at a high speed of 1100 r / min, then adding a leveling agent, an epoxy curing agent and a defoaming agent, stirring evenly, and obtaining a high-adhesion epoxy anti-corrosion coating.
[0057] Comparative Example 1
[0058] Compared with Example 4, the difference in Comparative Example 1 is that graphene replaces carboxylated graphene, and the other components, preparation steps and parameters are the same.
[0059] Comparative Example 2
[0060] Compared with Example 4, Comparative Example 2 is different in that eugenol is not used, and the other components, preparation steps and parameters are the same.
[0061] Comparative Example 3
[0062] Compared with Example 4, Comparative Example 3 is different in that thioglycerol is not used, and the remaining components, preparation steps and parameters are the same.
[0063] Comparative Example 4
[0064] Compared with Example 4, Comparative Example 4 is different in that p-fluorobenzenethiol is not used, and the remaining components, preparation steps and parameters are the same.
[0065] The coatings prepared in Examples 1-4 and Comparative Examples 1-4 were tested as follows, and the test results are shown in Table 1.
[0066] Adhesion test: GB / T9286-1998;
[0067] Pencil hardness test: GB / T6739-1996;
[0068] Salt water corrosion resistance test: CHI660E was used to test the salt water corrosion resistance of 10% NaCl for 30 days according to the method of GB1763-79;
[0069] Table 1
[0070]
[0071]
[0072] As can be seen from the test results of Table 1, compared with Comparative Examples 1-4, the coating prepared by the present invention has excellent adhesion, mechanical properties and good corrosion resistance. It can be seen from comparative analysis that the present invention creatively utilizes the rich active sites of carboxylated graphene, effectively promotes the embedding of eugenol molecules, and then realizes the grafting reaction of eugenol on carboxylated graphene, constructs a dense network structure, not only significantly improves the dispersion performance of graphene in epoxy resin system, but also plays the compatibilization effect between graphene and epoxy resin system, thereby greatly enhancing the mechanical properties of coating. Further, by grafting thioglycerol, the composite modified graphene is simultaneously equipped with carboxyl (-COOH) and hydroxyl (-OH), so that it can react with epoxy groups. The introduction of fluorine atoms can increase the volume of epoxy resin molecules, so that the interaction between epoxy resin molecules is enhanced, and a denser network structure is formed, thereby improving salt water corrosion resistance and mechanical properties. In addition, the hydrophobicity of the fluorinated epoxy resin helps prevent the penetration of salt through the resin film, further improving the salt water corrosion resistance. The rigid benzene ring structure introduced by fluorothiophenol and eugenol greatly increases the cross-linking density of the epoxy group system and forms a denser network structure. At the same time, the presence of the benzene ring structure effectively reduces the migration of fluorothiophenol and eugenol during the curing process and constructs a dense structure, thereby effectively improving the salt water corrosion resistance. In addition, the oxygen-containing groups on eugenol and thioglycerol further enhance the adhesion of the coating.
[0073] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high adhesion epoxy anticorrosion coating, characterized in that: The invention comprises the following components in parts by weight: 62-70 parts of epoxy resin, 5-8 parts of liquid petroleum resin, 7-12 parts of fumed silica, 6-8 parts of nano-montmorillonite, 5-8 parts of silane coupling agent, 0.1-0.3 parts of defoaming agent, 0.2-0.3 parts of epoxy curing agent, 7-10 parts of wetting agent, 0.5-1 parts of leveling agent, 7-10 parts of rutile titanium dioxide, 2-6 parts of aluminum silver paste, 6-9 parts of modified graphene and 70-80 parts of deionized water.
2. The high adhesion epoxy anticorrosion coating according to claim 1, characterized in that: The epoxy resin is bisphenol A epoxy resin; the silane coupling agent is silane coupling agent KH550.
3. The high adhesion epoxy anticorrosion coating according to claim 1, characterized in that: The wetting agent is polydimethylsiloxane; the defoaming agent is one or more of aliphatic polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ether, castor oil polyoxyethylene ether and fatty amine polyoxyethylene ether.
4. The high adhesion epoxy anticorrosion coating according to claim 1, characterized in that: The epoxy curing agent is methyl hexahydrophthalic anhydride; the leveling agent is BYK-111.
5. The high adhesion epoxy anticorrosion coating according to claim 1, characterized in that: The preparation method of the modified graphene comprises the following steps: 1) In an inert atmosphere, carboxylated graphene, anhydrous ethanol and eugenol are stirred and dispersed, a catalyst is added, heated and stirred, filtered, a solid is taken out for washing, and placed in an oven for vacuum drying to obtain prefabricated particles; 2) The prefabricated particles and anhydrous ethanol are mixed and then subjected to ultrasonic treatment, and a reaction monomer and a photoinitiator are added, stirred and mixed, filtered, and a solid is taken for washing, and placed in an oven for vacuum drying to obtain modified graphene.
6. The high adhesion epoxy anticorrosion coating according to claim 5, characterized in that: In step 1), the inert atmosphere is a nitrogen atmosphere; the stirring and dispersing is stirring at a speed of 700-800 r / min for 30-40 min; the heating and stirring is stirring at a temperature of 100-110° C. and a speed of 400-500 r / min for 2-3 h; the washing is washing three times with ethanol; and the vacuum drying is drying at a temperature of 80-90° C. to constant weight.
7. The high adhesion epoxy anticorrosive coating according to claim 5, characterized in that: In step 1), the mass ratio of the carboxylated graphene, anhydrous ethanol, eugenol and catalyst is 30-33:90-100:10-13:0.44-0.50; and the catalyst is p-toluenesulfonic acid.
8. The high adhesion epoxy anticorrosive coating according to claim 5, characterized in that: In step 2), the ultrasonic treatment is performed at a frequency of 200-300W for 12-20 minutes; the stirring and mixing is performed under 365nm ultraviolet irradiation at a temperature of 32-38°C for 5-7 hours; the washing is performed three times with ethanol; and the vacuum drying is performed at a temperature of 80-90°C to constant weight.
9. The high adhesion epoxy anticorrosive coating according to claim 5, characterized in that: In step 2), the mass ratio of the prefabricated particles, anhydrous ethanol, reaction monomer and photoinitiator is 40-50:140-160:4.2-6.0:0.22-0.30; the reaction monomer is prepared by mixing thioglycerol and p-fluorothiophenol in a mass ratio of 3:1; and the photoinitiator is photoinitiator 1173.
10. A method for preparing the high-adhesion epoxy anticorrosive coating according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: adding epoxy resin, fumed silica, nano-montmorillonite, rutile titanium dioxide, silane coupling agent, liquid petroleum resin, wetting agent, aluminum silver paste and modified graphene into deionized water, stirring evenly at a high speed of 900-1100 r / min, then adding a leveling agent, an epoxy curing agent and a defoaming agent, stirring evenly, and obtaining a high-adhesion epoxy anticorrosive coating.
Citation Information
Patent Citations
Shipping ballast cabin coating composition
CN101134867A
Liquid petroleum resin modified waterborne epoxy heavy-duty anticorrosion primer and preparation method thereof
CN108912952A
Waterborne epoxy anticorrosive paint containing composite functional modified graphene oxide and preparation method and application
CN113956746A
Water-based modified organic silicon high-temperature-resistant anticorrosive paint and preparation method thereof
CN114525078A
Waterborne polyurethane floor paint and preparation process thereof
CN118496700A